A Study on Local Resources and their Applicability in Classroom Instructions in Nepal (Rupandehi Campus Journal, 2024)
This study aims at identifying the applicability of locally available resources in school level classrooms instructions in general and analyzes the approaches, methods and techniques in classroom practices in study area. It also attempts to recommend some strategies for the application of local resources in classroom instructions for the development of practical education through functional or task-based classroom instructions. Based on qualitative method, the data have been collected through PRA, observation, and semi- structured interview. The collected data have been analyzed by using interpretative paradigm. The study has revealed abundances of locally available resources that can be applied in classroom instructions for the development of task-based, practical classroom instructions in study area and in general.